Position and potential of service-dominant logic - Evaluated in an ‘ism’ frame for further development - Löbler, Helge (Marketing theory, 2011)
This work offers a framework for researchers by linking service-dominant (S-D) logic to an intersubjective stream of philosophy of science. Service-dominant logic has resonated in marketing, but no existing research has attempted to link S-D logic with basic meta-theory to provide a framework. Since the range of philosophies of science (isms) referred to in the marketing literature is broad, varying from ‘realism’ to ‘relativism’, from ‘positivism’ to ‘constructivism’ and from ‘structuralism’ to ‘post-structuralism/postmodernism’, first the different isms are grouped into four main groups/streams and then S-D logic is analyzed and classified according to these streams. The four streams are: object-orientation (realism, positivism, empiricism, and so on); subject orientation (constructivism, interpretivism, and so forth); intersubjective orientation (social constructionism, pancritical rationalism, methodological constructivism, and so on); and sign orientation (post-structuralism, postmodernism, and variations). S-D logic is mainly underpinned by an intersubjective orientation and has a huge potential for further development both in and for marketing if seen from a sign-orientated, post-structural perspective and linked to the theory of practices.